IMMEDIATE DENTURE - Pocut Aya Sofya (Dentistry Faculty, 2017)
Tooth loss is an interrupt situation of aesthetic, function, psychology and social conditions for certain people, especially in patients with untenable teeth and should be extracted either several teeth or the entire teeth, moreover the anterior teeth. To avoid the toothless phase in patients that render the changes on face and interfere with daily activity, could be overcome by immediate denture. Immediate Denture is Full Denture/ Partial Denture used immediately right after extraction and in term of temporary.Keywords : Immediate denture, tooth lose, temporary denture